2020
DOI: 10.3390/su12177214
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Weak Governance in Grasslands and Wetlands of South America

Abstract: Weak governance is a major threat to sustainable development, especially in rural contexts and within ecosystems of great social and economic value. To understand and compare its arrangement in the grasslands and wetlands of the Colombian Llanos and the Paraguayan Pantanal, we build upon the Institutional and Development Framework (IAD) as we explore the role of political, economic, and social institutions and combine components of the theory of common-pool resources (CPR) and new institutional economics (NIE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 62 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…FNC [Federación Nacional de Cafeteros de Colombia] has shown that it is far more expensive to take a container from coffee growing in Armenia to Cartagena (900 km) than from In Brazil, coffee production involves complex governance mechanisms to coordinate the whole chain towards both domestic and international markets [21,40]. Although present in remote locations, the supply chain involves a supportive activity from private agents who collectively handle issues that government fails to address [30,41]. There is no public organization responsible for the sector in the country, but there are several associations and cooperatives that provide support to producers.…”
Section: Institutions and Infrastructurementioning
confidence: 99%
“…FNC [Federación Nacional de Cafeteros de Colombia] has shown that it is far more expensive to take a container from coffee growing in Armenia to Cartagena (900 km) than from In Brazil, coffee production involves complex governance mechanisms to coordinate the whole chain towards both domestic and international markets [21,40]. Although present in remote locations, the supply chain involves a supportive activity from private agents who collectively handle issues that government fails to address [30,41]. There is no public organization responsible for the sector in the country, but there are several associations and cooperatives that provide support to producers.…”
Section: Institutions and Infrastructurementioning
confidence: 99%
“…In Bole, the central government's bypassing of the assembly to fight against informal ASM in its territory suggests ambiguity regarding rule interpretation (e.g., Act 462 and Act 703) and enforcement. The central government's weak mechanism of stopping informal ASM through a militarized taskforce failed to defuse ASM operation in communities of Bole [10]. The disenfranchisement of district authorities in Bole and Talensi, makes them tolerate informal ASM and disregard SMCL's grievances by relaxing existing regulations and enforcement, leading to resource over exploitation and destruction of cashew farms, bodies of water, and forest reserves.…”
Section: Central Government Authorities Did Not Let Their Responsibilities Go To Local Peoplementioning
confidence: 99%
“…Customary law governs surface land rights while statutory laws and regulations govern subterranean mineral resources, leading to a situation where gold ore mining is the result of the interactions of customary law and government laws and regulations. This affects the governance and coordination of mineral wealth exploitation, which can positively or negatively affect resource sustainability [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Complimentary to this change in technology in the region, but often cited as the technological factor that will unlock the region for further soybean expansion, is the development and use of drought-resistant genetically modified (GM) seed technologies and glyphosate application (USDA-FAS 2018). As of 2019, over 340 soybean varieties had been tested in the Paraguayan Chaco with the most success seen in seed maturity groups with longer maturation periods (Dueck 2018). These dynamics will continue to play a role as production methods and seed genetics improve and are further specialized to conditions present in the region.…”
Section: Drivers Of Soybean Expansion In the Paraguayan Chacomentioning
confidence: 99%
“…This trend is particularly prevalent in the soybean sector, either through direct expansion into forest areas, or indirectly by displacing other agricultural activities-most notably cattle pastureland-to more marginal or forested areas (Gasparri et al 2016). These marginal expansion areas often exhibit poor governance systems and/or weak enforcement of socioenvironmental regulations (Eufemia et al 2020;Le Polain de Waroux et al 2016).…”
Section: Introductionmentioning
confidence: 99%